Quality of Life of Young Adults During The COVID-19 Pandemic - Magdalena ADAMCZYK-KOWALCZUK (Communications of International Proceedings, 2021)
Quality of life should not only be considered through the prism of material welfare, because it is also directly related to the individual’s mental sphere. The subjective aspect of quality of life is associated with well-being that provides contentment with life, as well as a satisfaction of needs such as social position, health, self-development or leisure activities. The crucial need during the COVID-19 pandemic was to protect lives and ensure health security. However, the time of the pandemic had also a negative impact in the areas of study, work, social relationships and leisure opportunities, and ultimately on the mental health. The purpose of this article is to verify the impact of the COVID-19 pandemic on the quality of life of young adults. The survey was conducted using the CAWI questionnaire with 155 participants. The results of the study show that during the COVID-19 pandemic, all the three aspects of the quality of young adults’ lives deteriorated.
Keywords: quality of life; satisfaction of material needs; contentment with life; COVID-19 pandemic